Synthesis of the first mixed ligand Mn (II) and Cd (II) complexes of 4-methoxy-pyridine-2-carboxylic acid, molecular docking studies and investigation of their anti-tumor effects in vitro - KILINÇ, OLCA; ORUN, OYA (WILEY, 2020)
The first mixed ligand Mn (II) and Cd (II) complexes containing 4-methoxy-pyridine-2-carboxylic acid (4-mpic) and 4,4 '-dimethyl-2,2 '-bipyridine (dmbpy) were synthesized in this study. The geometric structures of [Mn(4-mpic)(2)(dmbpy)] (complex 1) and [Cd(4-mpic)(2)(dmbpy)] (complex 2) were determined by single crystal X-Ray diffraction method. FT-IR and UV-Vis spectra were also recorded to investigate vibrational and electronic properties of complexes 1 and 2. Density functional theory (DFT) calculations were also carried out to provide a deep understanding in geometric, spectroscopic, electronic and nonlinear optical (NLO) properties of complexes 1 and 2. The first-order hyperpolarizibility (beta) parameter calculated as 332.9736 x 10(-30) esu demonstrated that complex 1 is an extremely promising candidate to NLO materials. Natural bond orbital (NBO) analysis not only verified the distorted octahedral geometries of central metal ions, but also found out the high-energy interactions responsible for biological activities for complexes 1 and 2. Anti-cancer activities of complexes 1 and 2 were tested on human breast carcinoma cell line MCF-7 (ER and PR positive, HER2 negative) and the triple negative breast carcinoma cell line MDA-MB 231 (ER, PR and HER2 negative). Dose-response relationship derived from MTT assays indicates that complexes 1 and 2 are showing concentration-dependent effects, which could suggest a potential use for these drug combinations in cancer cell lines.
Keywords: 4-methoxy-pyridine-2-carboxylic acid; anti-tumor activity; crystal structure; DFT; molecular docking; MAGNETIC-PROPERTIES; CRYSTAL-STRUCTURE; METAL-COMPLEXES; ANTICANCER ACTIVITY; COPPER(II) COMPLEX; ESCHERICHIA-COLI; CELL-DIVISION; DNA-BINDING; RESISTANCE; DFT